2007
DOI: 10.1007/s11661-007-9176-8
|View full text |Cite
|
Sign up to set email alerts
|

Crack-Tip Deformation Mechanisms in α-Fe and Binary Fe Alloys: An Atomistic Study on Single Crystals

Peter A. Gordon,
T. Neeraj,
Michael J. Luton
et al.

Abstract: Molecular statics simulations are employed using semiempirical interatomic interaction potentials to examine the near crack-tip deformation mechanisms in iron and iron alloy single crystals under pure mode-I loading. The deformation mechanisms are found to be strong functions of the crack orientation. For pure Fe systems, the sensitivity of the overall response is explored by comparing the behavior of a number of recently developed potentials. The competition between ductile and brittle responses is interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 24 publications
4
51
0
Order By: Relevance
“…(4)-(6), we use the surface energies computed by Gordon et al [2] and Müller et al [22] for the empirical potential employed here. These authors found values of 1.65 J/m 2 for f011g surfaces, 1.79 J/m 2 for f001g surfaces and 1.91 J/m 2 for f112g surfaces.…”
Section: Orientationmentioning
confidence: 99%
See 2 more Smart Citations
“…(4)-(6), we use the surface energies computed by Gordon et al [2] and Müller et al [22] for the empirical potential employed here. These authors found values of 1.65 J/m 2 for f011g surfaces, 1.79 J/m 2 for f001g surfaces and 1.91 J/m 2 for f112g surfaces.…”
Section: Orientationmentioning
confidence: 99%
“…Gordon et al [2] also calculated the unstable stacking fault energies for all slip systems in bcc Fe. Their results are given in Table 2.…”
Section: Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of single crystals, simulation specimens with four different crack orientations were prepared as indicated in Table 1 [32]. The number of total atoms in pure vanadium specimen is around 200,000 and given amounts (5, 20 at%) of hydrogen atoms are randomly distributed into the tetrahedral interstitial sites to generate hydrogen charged specimens.…”
Section: Hydrogen Effect On the Crack Propagationmentioning
confidence: 99%
“…Through the mode-I crack propagation and mode-II dislocation emission simulations, it can be concluded that the most promising mechanism of hydrogen embrittlement in Table 1 e Summary of crack orientations considered for mode-I fracture simulations [32]. q is the angle between the direction of crack propagation and the slip direction.…”
Section: 3mentioning
confidence: 99%